Personal Experiences of Women Surviving Breast Cancer as a Confrontation of the Meaning of the Women's Body - Abby Gina Boangmanalu; Atnike Nova Sigiro (Yayasan Jurnal Perempuan, 2019)
This study highlights the experiences faced by women breast cancer survivor in Jakarta in defining their bodies. Despite of medical assessment, breast cancer needs to be analyzed through feminist’s lense because breast cancer has close link with discourse of sexual body and engendered body. This study used a qualitative methodology that emphasizes critical analysis. Data collection was gathered through interviews with 8 women who are breast cancer survivors. The research reveals that under the normality of femininity of the patriarchal society, the women breast cancer survivors could confront the dominant interpretation upon women’s body